2009
DOI: 10.1162/jocn.2009.21127
|View full text |Cite
|
Sign up to set email alerts
|

Word Semantics Is Processed Even without Attentional Effort

Abstract: We examined the attentional modulation of semantic priming and the N400 effect for spoken words. The aim was to find out how the semantics of spoken language is processed when attention is directed to another modality (passive task), to the phonetics of spoken words (phonological task), or to the semantics of spoken words (word task). Equally strong behavioral priming effects were obtained in the phonological and the word tasks. A significant N400 effect was found in all tasks. The effect was stronger in the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 51 publications
5
16
0
Order By: Relevance
“…This interpretation is compatible with theories proposing that speech input activates lexical-semantic information as it unfolds, according to the match between the evolving input and representations in memory (e.g., Marslen-Wilson, 1987). The behavioral results also agree with electrophysiological findings in adults indicating that semantic access by speech, as indexed by the N400 potential, occurs even when the semantic content is irrelevant (e.g., Kutas & Federmeier, 2011; Relander, Rama, & Kujala, 2008). …”
Section: Semantic Access By Irrelevant Speechsupporting
confidence: 88%
“…This interpretation is compatible with theories proposing that speech input activates lexical-semantic information as it unfolds, according to the match between the evolving input and representations in memory (e.g., Marslen-Wilson, 1987). The behavioral results also agree with electrophysiological findings in adults indicating that semantic access by speech, as indexed by the N400 potential, occurs even when the semantic content is irrelevant (e.g., Kutas & Federmeier, 2011; Relander, Rama, & Kujala, 2008). …”
Section: Semantic Access By Irrelevant Speechsupporting
confidence: 88%
“…These findings support the N400 as a potential to detect higher cognitive functions that require directed attention and confirm previous studies showing strong attenuation or extinction of the N400 effect when attention is not directed toward the stimuli (McCarthy and Nobre, 1993; Chwilla et al, 1995). However, other studies did not find that N400 is modulated by the depth of processing level (Connolly, 1990; Relander et al, 2009). In their review, Deacon and Shelley-Tremblay (2000) concluded that the N400 does not necessarily require attention but only occurs if the processing of the stimuli is not actively inhibited.…”
Section: Discussionmentioning
confidence: 88%
“…We cannot definitely rule out this possibility, but it is unlikely to be an adequate alternative explanation of these data for several reasons. First, previous research indicates that LD leads to processing up to the semantic level, as indexed by modulations of the N400 component (e.g., Relander, Rama, & Kujala, 2009;Chwilla, Brown, & Hagoort, 1995), RT studies (see Neely, 1991) and overlapping neural correlates between more explicit semantic tasks and LD task (Ruff, Blumstein, Myers, & Hutchison, 2008). Second, the pseudowords were all phonotactically legal and all ended in the suffix indicating the infinitive in Dutch, which necessitates full reading of the verb to be able to perform the task.…”
Section: Discussionmentioning
confidence: 98%